(781) The Use of Regression Analysis In Economics of Education استخدام تحليل الانحدار في اقتصاديات التعليم - Abou Eldahab, Mohamed Galal (The Institute of National Planning, 2024)
In the last few years, a great deal of emphasis was given to education. This trend was noticed in the local, state, and national levels. This included all levels of education, elementary, secondary, as well as higher education. One reason to this emphasis may lie in the fact that the percentage of dropouts, in the recent years, has been increasing. This emphasis may be explained partly by the fact that a large part of the unemployed personnel is lacking the proper education and training. These emphases were also the result of the recognition that the return on investment in education is comparable, though .t may be greater, with that on impersonal investment, The realization, by the decision makers, of the positive relation be ;ween education and growth may be one of the reasons for this recent emphasis on education.